Implementation of International Regulations in Illegal Fishing: Case Study of Argentina and the Implementation of the Agreement on Port State Measures (PSMA) - Jenet Sheron Tikupadang; Agussalim Burhanuddin (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This research focuses on how international rules are put into practice to combat unlawful fishing, using Argentina as a case study and examining the use of the Port State Measures Agreement (PSMA). Information collected by the Food and Agriculture Organization in 2020 reveals that illegal fishing results in annual global economic losses ranging from USD 10 billion to USD 23 billion. The methodology employed in this study is descriptive analysis, with secondary data being utilised. The findings of this research highlight the existence of global laws such as UNCLOS 1982 and PSMA that aim to tackle illegal fishing. Unlike Indonesia, which has ratified the PSMA through Presidential Decree No. 43 of 2016, Argentina is the only Latin American country that has not ratified the PSMA. This is due to a dispute over the Malvinas Islands. However, the Argentine government has made efforts to reform national laws by implementing a fine system and collaborating between state institutions to address illegal fishing practices in the Argentine Exclusive Economic Zone.